WhatsApp Application:An Effective Tool for Out of-Class Activity - Nirgude, Manisha; Naik, Anil (Journal of Engineering Education Transformations, 2025)
In the digital era of education, use of ICT is found to be vital in different levels and different types of education to improve teaching-learning process. Now, due to rapid increase in smart phone and internet users a new paradigm shift in learning is m-learning. Even social networking and instant messengers become very much popular in communication and also in education. This study focuses on effective use of WhatsApp Application as an out-of-class activity for campus placement preparation for third year engineering students. Daily around 30-40 minutes WhatsApp Activity was conducted where one student posted technical questions after rigorous study and remaining students posted answers to these questions in 30 minutes duration. This was followed by assessment and discussions. This activity was completely of students for the students and by the students. After analysis, we found that students found more interest in WhatsApp activity and were more active in WhatsApp activity than In-class activity. During this activity students learnt managerial, technical and communication skills. Hence, WhatsApp can be used as an effective tool for out-of-class activity for multiple purposes like sharing information, assessment, discussions, feedback, flipped classroom concept etc.